2013
DOI: 10.4314/ahs.v13i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with depression and suicide among patients with diabetes mellitus and essential hypertension in a Nigerian teaching hospital

Abstract: Background: Diabetes mellitus (DM) and essential hypertension are chronic medical conditions that place a lot of burden on patients. The presence of depression and suicidal behaviour may worsen the prognosis. Objective: To assess the prevalence of depression and suicidal behaviour in subjects with diabetes mellitus and essential hypertension and also determine the socio-demographic correlates. Methods: Major depressive episode and suicidality modules of Mini-International Neuropsychiatric Interview were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 28 publications
5
34
2
1
Order By: Relevance
“…In this study, the prevalence of depression was found to be 24.19 %. The nding was in line with the cross-sectional study done in Ebinet,North west Ethiopia (17.5%) [9], Nigeria (26.7%) [10] and Saudi Arabia (20.7%) [11] . In our study being female were two times more likely to be depressed than male.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the prevalence of depression was found to be 24.19 %. The nding was in line with the cross-sectional study done in Ebinet,North west Ethiopia (17.5%) [9], Nigeria (26.7%) [10] and Saudi Arabia (20.7%) [11] . In our study being female were two times more likely to be depressed than male.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have documented a positive association between lack of employment and co-morbid depression in persons with DM (Friis and Nanjundappa, 1986; Igwe et al, 2013). A number of explanations could be responsible for these findings.…”
Section: Discussionmentioning
confidence: 93%
“…7 In patients with Diabetes and essential hypertension, the prevalence of depression and suicidal tendencies was studied and was found that depression and suicidal tendencies are found prominent in the diabetic patient as well as hypertensive, more being in the uneducated side. 8 Diabetes may be diagnosed and treated, but the depression in these patients goes unnoticed. Most of the time, depression is not considered an important factor, often ignored and left untreated.…”
Section: Introductionmentioning
confidence: 99%